PELAKSANAAN EVALUASI KEPALA TATA USAHA DALAM MENINGKATKAN KINERJA TENAGA KEPENDIDIKAN SEKOLAH MENENGAH KEJURUAN NEGERI DI PROVINSI JAMBI - Junita Nurul Hikmah; Sumirah Sumirah; Sri Ramdayeni Sakunti (Jurnal Manajemen Pendidikan, 2026)
The study aims to analyze the implementation of evaluations conducted by the Head of Administration to improve the performance] of educational staff in administrative services, and identify factors that support and hinder the implementation of evaluations in vocational high schools in Jambi Province. This study is qualitative study with a descriptive approach through observation and interviews. The results indicate that the implementation of evaluations by the Head of administration is carried out in a structured manner through the stages of evaluation planning, performance data collection, performance assessment, providing feedback, and follow-up in the form of coaching. The performance of educational staff in services is generally considered good, however, several educational staff still exhibited suboptimal levels of discipline, this affecting the smooth running of school administrative services. The findings also indicate several supporting and inhibiting factors, including clear performance standards, a technologi- based assessment system, and good communication between staff. The novelity of this study lies in the finding that the implementation of evaluations by the Head of administration influences the performance of educational staff ini school administrative services.